OP32 The gut virome-colonizing Orthohepadnavirus genus is associated with ulcerative colitis pathogenesis and induces intestinal inflammation in vivo. (30th January 2023) - Facoetti, A; Massimino, L; Palmieri, O; Fuggetta, D; Spanò, S; D'Alessio, S; Furfaro, F; D'Amico, F; ZIlli, A; Fiorino, G; Noviello, D; Latiano, A; et al.
Abstract: Background: Ulcerative colitis (UC) is a chronic inflammatory disorder with an unknown etiology 1 . Over recent years, a growing body of evidence has been pinpointing gut virome dysbiosis as a fundamental component in its progression 2, although its role during the early phases of chronic inflammation is far from being fully defined. Therefore, we sought to investigate the role of a virome-associated protein encoded by the Orthohepadnavirus genus, the Hepatitis B virus X protein (HBx) 3, during UC aetiopathogenesis. Methods: HBx positivity of UC patient-derived blood and gut mucosa was assessed by RT-PCR and Sanger sequencing correlated with clinical characteristics by multivariate analysis. Transcriptomics was performed on HBx-overexpressing endoscopic biopsies from healthy donors. C57BL/6 mice underwent intramucosal injections of liposome-conjugated HBx-encoding plasmids or the control. Multidimensional flow cytometry analysis was performed on colonic samples from HBx-treated and control animals. Transepithelial electrical resistance measurement, proliferation assay, ChIP-Seq, and RNA-Seq were performed on in vitro models of the gut barrier. Results: HBx was detected in about 45% of patients with UC (Figure 1) and found to induce colonic inflammation in mice (Figure 2A-2D), while its silencing reverted the colitis phenotype in vivo (Figure 2E-2H). HBx acts as a transcriptional regulator in epithelial cells (Figure 3), provoking barrier leakage and altering inflammatory response (Figures 3 and 4). Conclusion: This study paves the way for the understanding of the aetiopathogenesis of UC and provides a brand-new standpoint that looks at the virome as a target for tailored treatments, possibly leading to an entirely new approach to therapeutic intervention. References: 1. Massimino L, Lamparelli LA, Houshyar Y, et al. The Inflammatory Bowel Disease Transcriptome and Metatranscriptome Meta-Analysis (IBD TaMMA) framework. Nat Comput Sci 2021;1:511–5. doi:10.1038/s43588-021-00114-y 2. Ungaro F, Massimino L, D'Alessio S, et al. The gut virome in inflammatory bowel disease pathogenesis: From metagenomics to novel therapeutic approaches. United European Gastroenterol J 2019;7:999–1007. doi:10.1177/2050640619876787 3. Ungaro F, Massimino L, Furfaro F, et al. Metagenomic analysis of intestinal mucosa revealed a specific eukaryotic gut virome signature in early-diagnosed inflammatory bowel disease. Gut Microbes 2019;10:149–58. doi:10.1080/19490976.2018.1511664